Users’ experiences of park accessibility and attractiveness based on online review analytics - Abdelbaseer A. Mohamed; Jakub Kronenberg (Scientific Reports)
Abstract Understanding public experiences of urban parks is crucial for their sustainable and effective management. While traditional surveys demand substantial resources, social media data present a cost-effective approach to capturing people’s perceptions. This study utilizes Google reviews to examine users’ sentiments regarding Cairo’s urban parks. Using topic modeling, we identified four key themes: quality and maintenance, family and activities, costs and affordability, and natural environment. Sentiment analysis revealed that 79.8% of reviews expressed positive sentiments, while 8.1% were negative. Statistical analysis indicated that: (1) safety and commercialization-related factors like food and ticket prices significantly influence park accessibility; and (2) park attractiveness is strongly associated with the park’s cultural (e.g., aesthetic experiences, leisure and entertainment opportunities) and regulatory features (e.g., cleanliness, quietness). An in-depth content analysis validated these findings and added nuanced interpretation. These findings demonstrated that online reviews can serve as a valuable indicator of park accessibility and attractiveness, thereby fostering more informed park management decisions. However, we also acknowledge their limitations, such as potential bias towards more tech-savvy users and the lack of detailed demographic information. Therefore, future research should combine social media data with traditional qualitative methods to capture the broader socio-cultural dynamics influencing park use.